A Study Aesthetic Values In The Lyrics of The Song “Rejung Usul Seminggu” With Connection To Pancasila Values - sriwahyuningsih sriwahyuningsih (Jurnal Studi Sosial dan Politik, 2020)
This study aims to examine the moral message in the lyrics of popular song rejung recommended a week from the Semende area as a form of the application of Pancasila values ​​in the formation of characteristics in the study of aesthetic values ​​in the arts to form a character towards the values ​​towards nationality as practice in the principles of Pancasila .The research methodology is a qualitative descriptive regional song proposed by the week of rejung as a form of trust from God values ​​towards the formation of a trustful attitude given to people's representatives as a form of our obedience to our responsibilities as humans to God Almighty. symbolized in people's behavior through the song lyrics and qualitative research is one method to get the truth and classified as scientific research that is built on the basis of theories that develop from research and are controlled on an empirical basis.So in this qualitative research not only presents the data as it is but also seeks to interpret the correlation as an existing factor and also gives shape to the meaning of the moral message in the song's lyrics. Keywords: aesthetic value, song lyrics Pancasila values